Method for coating a workpiece substrate surface and coated workpiece

CN122979856APending Publication Date: 2026-10-27AVIC BEIJING AERONAUTICAL MFG TECH RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611469255.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0021]在本发明实施例所提供的镀膜工件,由工件基材、过渡层和纳米叠层构成,纳米叠包括交替设置的功能类金刚石膜层和过渡类金刚石膜层。沿背离工件基材的方向上,过渡层的硅含量逐渐减少、碳含量逐渐增加,硅含量的梯度设计,能够减少工件基材与过渡层的物性差异,提高过渡层与工件基材的结合力。功能类金刚石膜层和过渡类金刚石膜层交替设置,其中功能类金刚石膜层的硅含量和sp3碳含量均大于和过渡类金刚石膜层的硅含量和sp3碳含量,通过调控硅的掺杂,提高纳米叠层的韧性和硬度,从而综合提高了镀膜工件的使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979856A_ABST
    Figure CN122979856A_ABST
Patent Text Reader

Abstract

The application discloses a film plating method on a workpiece substrate surface and a film-plated workpiece, relates to the field of material film plating, and comprises the following steps: providing a workpiece substrate; forming a transition layer on the surface of the workpiece substrate to be plated, wherein the silicon content of the transition layer gradually decreases and the carbon content gradually increases in the direction away from the surface to be plated; forming a nano-laminate on the transition layer to obtain an initial workpiece, the nano-laminate comprises alternately arranged functional diamond-like carbon film layers and transition diamond-like carbon film layers, the nano-laminate comprises at least two functional diamond-like carbon film layers, silicon is doped in the functional diamond-like carbon film layers and the transition diamond-like carbon film layers, the mass percentage of silicon in the functional diamond-like carbon film layers is greater than that in the transition diamond-like carbon film layers; and a magnetic field and an electric field are applied to the initial workpiece according to a set rule and maintained for a set time to obtain a target workpiece. The application can prepare a thin film with better integrity and longer service life on the surface of the workpiece substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of material coating technology, and more specifically to a method for coating a workpiece substrate. Background Technology

[0002] In some fields where high wear resistance of materials is required, it is often necessary to coat the surface of the substrate. For example, in the aerospace, high-precision equipment, automotive parts, and semiconductor mold industries, diamond-like carbon (DLC) films are often deposited on the surface of the substrate.

[0003] Specifically, silicon-containing DLC ​​films have better high-temperature resistance and corrosion resistance due to the doping of silicon, and also have higher hardness and lower coefficient of friction.

[0004] However, how to prepare silicon-containing DLC ​​films with better integrity and longer service life on the surface of substrates has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] This invention aims to address, to a certain extent, one of the technical problems in related technologies. To this end, this invention provides a method for depositing a film on the surface of a workpiece substrate and a deposited workpiece. This method can prepare a film with better integrity and a longer service life on the surface of the workpiece substrate.

[0006] As a first aspect of the present invention, a method for depositing a film on the surface of a workpiece substrate is provided, the method comprising: Provide workpiece substrate; A transition layer is formed on the surface of the workpiece substrate to be coated, wherein, along the direction away from the surface of the film to be coated, the silicon content of the transition layer gradually decreases and the carbon content gradually increases; A nanolayer is formed on the transition layer to obtain an initial workpiece. The nanolayer includes alternating functional diamond-like carbon (DLC) films and transitional DLC films, and the nanolayer includes at least two of the functional DLC films. Both the functional DLC films and the transitional DLC films are doped with silicon, and the mass percentage of silicon in the functional DLC films is greater than the mass percentage of silicon in the transitional DLC films. A magnetic field and an electric field are applied to the initial workpiece according to a set rule and maintained for a set time to obtain the target workpiece. In the target workpiece, the mass percentage of silicon in the functional diamond-like carbon film is greater than the mass percentage of silicon in the transition diamond-like carbon film. The SP content in the functional diamond-like carbon film... 3 The mass percentage of carbon is greater than that of sp in the transition diamond-like carbon film. 3 The percentage of carbon by mass.

[0007] Optionally, the initial workpiece is disposed between two power supply electrodes and located in a magnetic field generated by a magnetic field assembly comprising a plurality of movable coils with the axial directions of the plurality of coils aligned, and the initial workpiece is disposed within a cavity defined by the plurality of coils. In the step of applying a magnetic field and an electric field to the initial workpiece according to the set rules, the position of each coil is determined according to the set rules, and the power supply electrode and the magnetic field assembly are powered by a pulsed DC power supply.

[0008] Optionally, the duty cycle of the pulsed DC power supply is between 30% and 60%, the 10 pulse widths of the pulsed DC power supply are between 50μs and 100μs, the frequency is between 1Hz and 50Hz, and the voltage is between 350V and 400V, so that the electric field strength is between 10V and 20V and the magnetic field strength is between 1T and 2T.

[0009] Optionally, the set time is between 5 minutes and 25 minutes.

[0010] Optionally, a nanolayer stack is formed on the transition layer, comprising the following alternating steps: A functional diamond-like carbon (DLC) film is formed, wherein the silicon content in the DLC film is between 5 wt% and 15 wt%, and sp... 3 The carbon content is between 60 wt% and 75 wt%. A transition diamond-like carbon (LDC) film is formed, wherein the silicon content in the transition diamond-like carbon film is between 1 wt% and 5 wt%, and sp... 3 The carbon content is between 50wt% and 60wt%.

[0011] Optionally, in the step of forming the functional diamond-like film, a protective gas, a first process gas, and a second process gas are introduced into the process chamber, wherein the first process gas contains silicon and the second process gas contains carbon. In the step of forming the transition diamond-like carbon film, the protective gas and the second process gas are introduced into the process chamber.

[0012] Optionally, the protective gas includes argon, the first process gas includes tetramethylsilane, and the second process gas includes acetylene; In the step of forming the functional diamond-like carbon film, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the first process gas is between 10 sccm and 12 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is between 1.0 Pa and 2.0 Pa, and the bias power supply in the process chamber is between 120 V and 150 V. In the step of forming the transition diamond-like carbon film, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is between 1.0 Pa and 2.0 Pa, and the bias power supply in the process chamber is between 120 V and 150 V.

[0013] Optionally, the single-layer thickness of both the functional diamond-like carbon film and the transition diamond-like carbon film is between 5 nm and 25 nm. The functional diamond-like carbon film and the transitional diamond-like carbon film are stacked alternately to form 5 to 20 cycles.

[0014] Optionally, a transition layer is formed on the surface of the workpiece substrate to be coated, including: A protective gas is introduced into the process chamber and the protective gas is plasma-ionized to perform plasma cleaning on the workpiece substrate. In a protective gas atmosphere, a first process gas is introduced into the process chamber and deposited on the workpiece substrate, wherein the first process gas contains silicon. In the atmosphere of the protective gas, the first process gas and the second process gas are introduced into the process chamber and deposited on the workpiece substrate, wherein the second process gas contains carbon; In the atmosphere of the protective gas, the second process gas is introduced into the process chamber and deposited on the workpiece substrate.

[0015] Optionally, the protective gas includes argon, the first process gas includes tetramethylsilane, and the second process gas includes acetylene; Before the step of plasmaing the protective gas, the process chamber is first evacuated to ensure that the pressure inside the process chamber does not exceed 8 × 10⁻⁶. -3 Pa, In the step of plasmaing the protective gas, the pressure in the process chamber is maintained between 0.3 Pa and 1.2 Pa, the flow rate of the protective gas is between 140 sccm and 160 sccm, and the voltage of the bias power supply is between 500 V and 1500 V; In the step of depositing a first process gas on the workpiece substrate under a protective gas atmosphere, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the first process gas is between 10 sccm and 12 sccm, the pressure in the process chamber is maintained between 1.0 Pa and 2.0 Pa, and the voltage of the bias power supply is between 120 V and 150 V. In the step of introducing the first process gas and the second process gas into the process chamber under the atmosphere of the protective gas, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the first process gas is between 10 sccm and 12 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is maintained between 1.0 Pa and 2.0 Pa, and the bias voltage is between 120 V and 150 V. In the step of depositing the second process gas on the workpiece substrate by introducing the second process gas into the process chamber under the atmosphere of the protective gas, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is maintained between 1.0 Pa and 2.0 Pa, and the bias voltage is between 120 V and 150 V.

[0016] Optionally, in the step of applying a magnetic field and an electric field to the initial workpiece according to a set rule, the pressure inside the process chamber is between 1 Pa and 5 Pa, and the temperature inside the process chamber does not exceed 400°C.

[0017] In the method for coating a workpiece substrate surface provided in this embodiment of the invention, a transition layer is first formed on the workpiece substrate surface through a deposition process, and then a nanolayer consisting of alternating functional diamond-like carbon (DLC) films and transition DLC films is formed on the surface of the transition layer through an alternating deposition process. A magnetic field and an electric field are applied to the coated workpiece, and through the synergistic effect of electromagnetic force and Joule heating, the movement of local elements and defects is achieved, resulting in stress release, interface optimization, and structural densification. The resulting coated workpiece exhibits good integrity and a longer service life.

[0018] As a second aspect of the present invention, a coated workpiece is provided, the coated workpiece being prepared by the method of the first aspect. The coated workpiece includes a workpiece substrate, and further includes a transition layer disposed on one surface of the workpiece substrate, and a nanolayer disposed on the side of the transition layer opposite to the workpiece substrate. Along the direction opposite to the surface to be coated, the silicon content of the transition layer gradually decreases and the carbon content gradually increases. The nanolayer includes alternately arranged functional diamond-like carbon (DLC) films and transition DLC films. In the coated workpiece, the mass percentage of silicon in the functional DLC films is greater than the mass percentage of silicon in the transition DLC films. The silicon content in the functional DLC films is... 3 The mass percentage of carbon is greater than that of sp in the transition diamond-like carbon film. 3 The percentage of carbon by mass.

[0019] Optionally, in the functional diamond-like carbon film, the silicon content is between 5 wt% and 15 wt%, sp 3 The carbon content is between 60 wt% and 75 wt%, and the silicon content in the transition diamond-like carbon film is between 1 wt% and 5 wt%. 3 The carbon content is between 50wt% and 60wt%.

[0020] Optionally, the thickness of the transition layer is between 100 nm and 300 nm; The nanolayer comprises 5-20 layers of the functional diamond-like carbon film and 5-20 layers of the transition diamond-like carbon film; The thickness of the functional diamond-like carbon film is between 5 nm and 25 nm; the thickness of the transition diamond-like carbon film is between 5 nm and 25 nm.

[0021] The coated workpiece provided in this embodiment of the invention comprises a workpiece substrate, a transition layer, and a nanolayer stack. The nanolayer stack includes alternating functional diamond-like carbon (DLC) films and transition DLC films. Along the direction away from the workpiece substrate, the silicon content of the transition layer gradually decreases while the carbon content gradually increases. This gradient design of silicon content reduces the difference in physical properties between the workpiece substrate and the transition layer, improving the adhesion between them. The functional DLC films and transition DLC films are alternately arranged, wherein the silicon content and carbon content of the functional DLC films are... 3 The carbon content is greater than that of the silicon content and sp content of transition diamond-like carbon films. 3 By adjusting the carbon content and silicon doping, the toughness and hardness of the nanolayers are improved, thereby comprehensively increasing the service life of the coated workpiece.

[0022] The reasoning process for the beneficial effects of the coated workpiece provided by this invention is similar to that of the aforementioned method for coating the surface of a workpiece substrate, and will not be repeated here.

[0023] These features and advantages of the present invention will be disclosed in detail in the following specific embodiments and accompanying drawings. The preferred embodiments or means of the present invention will be shown in detail in conjunction with the accompanying drawings, but are not intended to limit the technical solutions of the present invention. In addition, each of these features, elements and components appearing in the following text and drawings is a plurality of, and different symbols or numbers are used for convenience of representation, but all represent parts with the same or similar construction or function. Attached Figure Description

[0024] The present invention will be further described below with reference to the accompanying drawings: Figure 1 This is a flowchart illustrating a method for preparing a film on the surface of a workpiece substrate according to an embodiment of the present invention. Figure 2 This is a schematic diagram of the structure of the coated workpiece provided in an embodiment of the present invention; Figure 3 A schematic diagram of electromagnetic composite post-processing of a coated workpiece provided in an embodiment of the present invention; Figure 4 A schematic diagram of the atomic structure of the coated workpiece before and after composite electromagnetic post-treatment provided in an embodiment of the present invention; Figure 5 This is a flowchart of a method for preparing a nanolayer stack on a transition layer according to an embodiment of the present invention; Figure 6 A flowchart illustrating a method for forming a transition layer on the surface of a workpiece substrate to be coated, provided in an embodiment of the present invention. Figure 7 Scanning electron microscope (SEM) images of the thin film cross-section before and after composite electromagnetic post-processing provided in an embodiment of the present invention; Figure 8 Raman spectra of the thin films before and after composite electromagnetic post-treatment provided in an embodiment of the present invention; Figure 9 This is a scratch test curve of a coated workpiece before and after composite electromagnetic post-treatment, provided in an embodiment of the present invention. Figure 10 The friction coefficient-time curves of coated workpieces under different composite electromagnetic post-treatment conditions are provided in the embodiments of the present invention.

[0025] Figure label: 10. Workpiece substrate; 20. Transition layer; 30. Nanolayer; 31. Functional diamond-like carbon film; 32. Transition diamond-like carbon film; 110. Coil; 200. Power supply electrode. Detailed Implementation

[0026] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described are intended to explain the present invention and should not be construed as limiting the invention.

[0027] The terms "an embodiment," "example," or "trademark" used in this specification refer to a particular feature, structure, or characteristic described in connection with the embodiment itself that may be included in at least one embodiment disclosed in this invention. The phrase "in an embodiment" appearing in various places throughout the specification does not necessarily refer to the same embodiment.

[0028] As a first aspect of the present invention, a method for coating a workpiece substrate surface is provided, wherein, as Figure 1 As shown, the method includes: In step S110, a workpiece substrate is provided; In step S120, a transition layer is formed on the surface of the workpiece substrate to be coated, wherein, along the direction away from the surface of the film to be coated, the silicon content of the transition layer gradually decreases and the carbon content gradually increases; In step S130, a nano-stack is formed on the transition layer to obtain an initial workpiece. The nano-stack includes alternating functional diamond-like carbon (DLC) films (i.e., Si-DLC) and transition diamond-like carbon (C-DLC) films, and the nano-stack includes at least two of the functional DLC films. Both the functional DLC films and the transition diamond-like carbon (C-DLC) films are doped with silicon, and the mass percentage of silicon in the functional DLC films is greater than the mass percentage of silicon in the transition diamond-like carbon (C-DLC) films. In step S140, a magnetic field and an electric field are applied to the initial workpiece according to a set rule and maintained for a set time to obtain the target workpiece.

[0029] In the target workpiece, the mass percentage of silicon in the functional diamond-like carbon film is greater than the mass percentage of silicon in the transition diamond-like carbon film, and the amount of silicon in the functional diamond-like carbon film is greater than that in the transition diamond-like carbon film. 3 The mass percentage of carbon is greater than that of sp in the transition diamond-like carbon film. 3 The percentage of carbon by mass.

[0030] The workpiece substrate is mostly made of metallic materials, which have significantly different physical properties from those of the diamond-like carbon film. In the embodiments of this application, such as... Figure 2 As shown, before forming the nanolayer 30, a transition layer 20 is first formed on the workpiece substrate 10. This gradually reduces the differences in physical properties and hardness between the transition layer and the diamond-like carbon (DLC) film, improving the film-substrate adhesion (i.e., the overall adhesion between the combined structure of the transition layer 20 and the nanolayer 30 and the workpiece substrate 10) and reducing the internal stress of each film layer in the target workpiece. Then, the nanolayer 30 is formed on the transition layer 20. A transition DLC film 32 is formed between two adjacent functional DLC film layers 31 in the nanolayer 30. It is understood that silicon doping can improve the hardness and wear resistance of the nanolayer. Furthermore, because the nanolayer includes a transition DLC film 32 with a relatively low silicon doping content, the nanolayer possesses good toughness, comprehensively improving its service life and meeting the long-term service requirements of the target workpiece.

[0031] In addition, in step S140, electromagnetic coupling post-processing can be performed on the workpiece to further improve defects at the interfaces of each film layer and to further diffuse elements at the interfaces of each film layer. Specifically, by superimposing electric and magnetic fields onto the initial workpiece with the transition layer and nanolayer stack, the fields can be directly applied to the surface and interlayer of the workpiece. Through the synergistic effect of electromagnetic force and Joule heating, the movement of local elements and defects can be achieved, thereby realizing stress release, interface optimization, and structural densification. Performing electromagnetic coupling post-processing after the film deposition is completed can ensure the integrity of each film layer and prevent film failure caused by graphitization at high temperatures exceeding 400°C, further improving the service life of the target workpiece.

[0032] Furthermore, the post-processing of the magnetic field and electric field in step S140 can make the mass percentage of silicon in the functional diamond-like carbon film layer greater than the mass percentage of silicon in the transition diamond-like carbon film layer, and the silicon content in the functional diamond-like carbon film layer... 3 The mass percentage of carbon is greater than that of sp in the transition diamond-like carbon film. 3 The percentage of carbon by mass. In functional diamond-like carbon (DLC) films, the Si-C covalent bonds are a high-temperature resistant bonding structure. Due to the high Si-C covalent bond content, elemental diffusion and interlayer oxidation are less likely to occur at temperatures exceeding 400°C. Consequently, the target workpiece is more suitable for the service requirements of high-temperature environments such as aerospace.

[0033] In other words, by setting a transition layer, the adhesion between the film and the workpiece substrate can be improved and the internal stress between the film layers can be reduced. The alternating functional diamond-like carbon (DLC) film layers and transitional DLC film layers improve the hardness and wear resistance of the film while also improving the overall toughness, thereby increasing the overall service life of the film. Finally, the deposited film is subjected to electromagnetic coupling post-treatment. The electric field and magnetic field work together with electromagnetic force and Joule heating to improve the interfacial defects of the film layer, promote element diffusion, release stress, densify the structure, protect the integrity of the film layer, and inhibit high-temperature graphitization failure.

[0034] In this embodiment of the invention, no special restrictions are placed on the "setting rules", as long as the defects at the film interface can be eliminated.

[0035] As an optional implementation, a pulsed electric field and an axial magnetic field can be applied to the initial workpiece.

[0036] Specifically, such as Figure 3As shown, the initial workpiece is positioned between two power supply electrodes 200 and located in a magnetic field, which is generated by a magnetic field assembly comprising multiple movable coils 110, the axial directions of the multiple coils 110 being aligned, and the initial workpiece is positioned within a cavity defined by the multiple coils 110.

[0037] In this embodiment of the invention, in the step of applying a magnetic field and an electric field to the initial workpiece according to a set rule, the position of each coil is determined according to the set rule, and different pulsed DC power supplies are used to supply power to the power supply electrode and the magnetic field assembly respectively.

[0038] The bipolar pulsed electric field relies on energy storage capacitors and power switches to control the direction of the series discharge current, generating an alternating positive and negative pulse sequence with independently adjustable amplitude and pulse width. The duty cycle and timing of the positive and negative electric fields can be set, dynamically adjusting the accumulated charge and regulating the thermoelectric effect, thus solving the problems of charge accumulation and thermal effects in unipolar electric fields. The axial gradient magnetic field can be coupled using Maxwell coils, generating a gradient magnetic field by moving the coil position and adjusting the current. The electric and magnetic fields act together on the workpiece surface and between layers. Through the synergistic effect of electromagnetic force, Joule heating, and plasma excitation, magnetic field lines penetrate the workpiece interior, driving the migration of interface elements and defects. The axial gradient change in magnetic induction intensity concentrates the electromagnetic force in key areas, achieving efficient electromagnetic field coupling and precise control of the movement of electrons, ions, and particles.

[0039] like Figure 4 As shown, the left side shows the film structure after deposition without electromagnetic composite post-treatment. The boundaries of each film layer are distinct, and there is no obvious diffusion behavior of elements at the interface. The interface defects remain in situ. The right side shows the film structure after electromagnetic composite post-treatment. Under the synergistic effect of electric and magnetic fields, element diffusion and defect migration occur at the interlayer interfaces between the workpiece substrate 10 and the transition layer 20, as well as between the transition layer 20 and the nano-stack 30. Atoms at the interface permeate each other, reducing defect distribution, optimizing the interface bonding state, releasing residual stress inside the film, and improving the overall structural integrity and bonding strength of the film.

[0040] As an optional implementation, the duty cycle of the pulsed DC power supply is between 30% and 60%, the pulse width of the 10 pulses of the pulsed DC power supply is between 50μs and 100μs, the frequency is between 1Hz and 50Hz, and the voltage is between 350V and 400V, so that the electric field strength is between 10V and 20V and the magnetic field strength is between 1T and 2T.

[0041] In this embodiment of the invention, there are no special requirements for the set time, as long as it can eliminate defects at the film interface. Optionally, the set time is between 5 minutes and 25 minutes.

[0042] As described above, the nanolayer comprises a functional diamond-like carbon film layer and a transition diamond-like carbon film layer stacked together. Accordingly, a nanolayer is formed on the transition layer, such as... Figure 5 As shown, the steps are performed alternately: In step S131, a functional diamond-like carbon (DLC) film is formed, wherein the silicon content in the DLC film is between 5 wt% and 15 wt%, and sp... 3 The carbon content is between 60 wt% and 75 wt%. In step S132, a transition diamond-like carbon (LDC) film is formed, wherein the silicon content in the transition diamond-like carbon film is between 1 wt% and 5 wt%, and sp... 3 The carbon content is between 50wt% and 60wt%.

[0043] In this embodiment of the invention, a nanolayer is formed by alternately depositing the two types of films. The functional diamond-like carbon (DLC) film has a higher silicon content and sp³ carbon ratio, ensuring basic hardness and load-bearing capacity. The transitional DLC film, with a relatively lower silicon content and sp³ carbon ratio, possesses excellent toughness and is disposed between adjacent functional DLC films, serving as a stress buffer layer to disperse residual stress within the film. The alternating stacking of the two film layers mitigates the interfacial stress caused by abrupt changes in the composition of a single film layer, improves interlayer bonding, reduces interlayer defects, and achieves a synergistic improvement in film hardness, toughness, and wear resistance.

[0044] Optionally, in the step of forming a functional diamond-like film, a protective gas, a first process gas, and a second process gas are introduced into the process chamber, wherein the first process gas contains silicon and the second process gas contains carbon. In the step of forming the transition diamond-like carbon film, the protective gas and the second process gas are introduced into the process chamber.

[0045] The protective gas includes argon, the first process gas includes tetramethylsilane, and the second process gas includes acetylene. In the step of forming the functional diamond-like carbon film, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the first process gas is between 10 sccm and 12 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is between 1.0 Pa and 2 Pa, and the bias power supply in the process chamber is between 120 V and 150 V. In the step of forming the transition diamond-like carbon film, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is between 1.0 Pa and 2 Pa, and the bias power supply in the process chamber is between 120 V and 150 V.

[0046] In this embodiment of the invention, a deposition process is used to deposit a film on the surface of a workpiece substrate. Tetramethylsilane gas is used as the silicon source, acetylene gas is used as the carbon source, and argon gas is used as the protective gas. By switching the gas components and precisely controlling the process parameters, high silicon doped functional diamond-like carbon film and low silicon doped transition diamond-like carbon film are prepared respectively.

[0047] Optionally, the thickness of both the functional diamond-like carbon film and the transition diamond-like carbon film is between 5 nm and 25 nm. This avoids stress concentration due to excessive thickness or compositional confusion caused by excessive thinness of the single layer.

[0048] Optionally, the functional diamond-like carbon (DLC) film and the transitional diamond-like carbon (DLC) film are alternately stacked to form 5 to 20 cycles. That is, in the nanolayer stack, there are approximately 5 to 20 functional DLC film layers and approximately 5 to 20 transitional DLC film layers.

[0049] In this embodiment of the invention, the total thickness of the nanolayer stack and the number of interfaces can be flexibly adjusted. When the number of cycles is too small, the number of interlayer interfaces is insufficient, stress is dispersed, and it is difficult to fully release the residual stress of the film. When the number of cycles is too large, the overall deposition time increases, the preparation efficiency decreases, and it is also easy to accumulate defects between multiple layers, increasing the difficulty of process control.

[0050] Optionally, such as Figure 6 As shown, forming a transition layer on the surface of the workpiece substrate to be coated includes the following steps: In step S121, a protective gas is introduced into the process chamber and the protective gas is plasma-ionized to perform plasma cleaning on the workpiece substrate. In step S122, under a protective gas atmosphere, a first process gas is introduced into the process chamber and deposited on the workpiece substrate, wherein the first process gas contains silicon. In step S123, under the atmosphere of the protective gas, the first process gas and the second process gas are introduced into the process chamber for deposition on the workpiece substrate, wherein the second process gas contains carbon. In step S124, under the atmosphere of the protective gas, the second process gas is introduced into the process chamber and deposited on the workpiece substrate.

[0051] The protective gas includes argon, the first process gas includes tetramethylsilane, and the second process gas includes acetylene. Before the step of plasmaing the protective gas, the process chamber is first evacuated to ensure that the pressure inside the process chamber does not exceed 8 × 10⁻⁶. -3 Pa, In the step of plasmaing the protective gas, the pressure in the process chamber is maintained between 0.3 Pa and 1.2 Pa, the flow rate of the protective gas is between 140 sccm and 160 sccm, and the voltage of the bias power supply is between 500 V and 1500 V; In the step of depositing a first process gas on the workpiece substrate under a protective gas atmosphere, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the first process gas is between 10 sccm and 12 sccm, the pressure in the process chamber is maintained between 1.0 Pa and 2.0 Pa, and the voltage of the bias power supply is between 120 V and 150 V. In the step of introducing the first process gas and the second process gas into the process chamber under the atmosphere of the protective gas, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the first process gas is between 10 sccm and 12 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is maintained between 1.0 Pa and 2.0 Pa, and the bias voltage is between 120 V and 150 V. In the step of depositing the second process gas on the workpiece substrate by introducing the second process gas into the process chamber under the atmosphere of the protective gas, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is maintained between 1.0 Pa and 2.0 Pa, and the bias voltage is between 120 V and 150 V.

[0052] In this embodiment of the invention, before performing plasma cleaning on the workpiece substrate, the workpiece substrate is pretreated by first polishing the material surface. Specifically, 200# sandpaper, 400# sandpaper, 800# sandpaper, 1200# sandpaper, 2000# sandpaper and polishing cloth with polishing agent are used sequentially to polish the workpiece substrate. Then, ultrasonic cleaning or alcohol cleaning is used to clean the material surface of the polished workpiece substrate to remove surface deposits, resulting in a clean workpiece substrate.

[0053] In the plasma cleaning step of the workpiece substrate, the plasma cleaning process lasts for 30 to 50 minutes. The deposition stage can employ thin film preparation processes such as PECVD and magnetron sputtering. The deposition time is adjusted according to the required thickness.

[0054] Optionally, in the step of applying a magnetic field and an electric field to the initial workpiece according to the set rules, the pressure in the process chamber is between 1 Pa and 5 Pa, which serves to dilute and protect the plasma; the temperature in the process chamber does not exceed 400°C to avoid thin film graphitization and promote ion rearrangement.

[0055] As a second aspect of the present invention, a coated workpiece is provided, the coated workpiece comprising a workpiece substrate, wherein the coated workpiece is a workpiece obtained by coating the workpiece substrate using the method provided in the first aspect of the present invention. Specifically, the coated workpiece further comprises a transition layer disposed on one side surface of the workpiece substrate, and a nanolayer disposed on the side of the transition layer opposite to the workpiece substrate, wherein, along the direction opposite to the surface to be coated, the silicon content of the transition layer gradually decreases and the carbon content gradually increases, and the nanolayer comprises alternating functional diamond-like carbon (DLC) film layers and transition DLC film layers.

[0056] The functions and beneficial effects of the coated workpiece have been described in detail above, and will not be repeated here.

[0057] Optionally, in the functional diamond-like carbon film, the silicon content is between 5 wt% and 15 wt%, sp 3 The carbon content is between 60 wt% and 75 wt%, and the silicon content in the transition diamond-like carbon film is between 1 wt% and 5 wt%. 3 The carbon content is between 50wt% and 60wt%.

[0058] Optionally, the thickness of the transition layer is between 100 nm and 300 nm. This thickness of the transition layer can adequately buffer the abrupt changes in physical properties and hardness between the metal workpiece substrate and the nanolayer, effectively alleviate the internal stress between the film layers, avoid insufficient stress buffering and interface bonding failure caused by an excessively thin transition layer, and also prevent the accumulation of internal stress and film cracking and detachment caused by an excessively thick transition layer, thus ensuring that the transition layer plays a gradient transition role.

[0059] Optionally, the nanolayer comprises 5-20 layers of the functional diamond-like carbon film and 5-20 layers of the transition diamond-like carbon film.

[0060] Optionally, the thickness of the functional diamond-like carbon film is between 5 nm and 25 nm; the thickness of the transition diamond-like carbon film is between 5 nm and 25 nm.

[0061] Example Example 1: The surface of the workpiece substrate is treated by grinding and polishing. Specifically, the workpiece substrate is treated by grinding and polishing in sequence with 200# sandpaper, 400# sandpaper, 800# sandpaper, 1200# sandpaper, 2000# sandpaper and polishing cloth with polishing agent.

[0062] The surface of the workpiece substrate after grinding and polishing is cleaned by means of ultrasonic cleaning or alcohol wiping to remove surface adhering substances and obtain a clean workpiece substrate.

[0063] The cleaned workpiece substrate is placed into the process chamber of the PECVD deposition equipment to form a transition layer on the surface of the workpiece substrate to be coated. This process specifically includes: Evacuate the process chamber until the pressure is less than 6 × 10⁻⁶. -3 Pa, argon gas is introduced as a protective gas and plasma is ionized. During this process, the flow rate of argon gas is 150 sccm, the chamber pressure is adjusted to 1 Pa, the bias voltage is 1000 V, and the plasma cleaning is performed for 35 min. Argon flow rate is adjusted to 100 sccm, and tetramethylsilane is introduced into the process chamber as the first process gas for coating. The flow rate of tetramethylsilane is 10 sccm, the pressure in the process chamber is 1.5 Pa, the bias power supply is 150 V, and the coating time is 30 min. Argon flow rate is adjusted to 100 sccm. Tetramethylsilane is used as the first process gas and acetylene is used as the second process gas and introduced into the process chamber for coating. The flow rate of tetramethylsilane is 10 sccm and the flow rate of acetylene is 90 sccm. The pressure in the process chamber is 1.8 Pa, the bias power supply is 120 V, and the coating time is 15 min. Argon flow rate was adjusted to 100 sccm, tetramethylsilane flow rate was adjusted to 0 sccm, and acetylene was introduced into the process chamber as the second process gas for coating. The acetylene flow rate was 90 sccm, the pressure in the process chamber was 1.8 Pa, the bias power supply was 120 V, and the coating time was 15 min to obtain the transition layer.

[0064] Five deposition cycles were used to alternately deposit Si-DLC and C-DLC, with a total thickness of 100 nm per cycle; each Si-DLC layer was 50 nm thick; and each C-DLC layer was 50 nm thick.

[0065] The deposited thin film sample undergoes composite electromagnetic post-processing. The sample is clamped between two power supply electrodes 200 and surrounded by coils 110 (see...). Figure 3After clamping and positioning, power is supplied to the power supply electrode 200 and the coil 110 respectively, and composite electromagnetic post-processing is performed in the process chamber, specifically including: In a vacuum environment, 10 sccm of argon gas is introduced, and the temperature is controlled to not exceed 200℃ and maintained at a constant temperature. The electric field power supply uses a pulsed DC power supply with a duty cycle between 30% and 60%, and the pulse width of the 10 pulses is between 50μs and 100μs, with a frequency between 1Hz and 50Hz. The impedance of the magnetic field coil is between 2Ω and 8Ω, and it is powered by 380V / 50Hz AC. It is equipped with a 0-10V DC adjustable control signal. The electric field strength is adjusted to 10V, and the magnetic field strength is 1.5T. The post-processing is maintained for 10 minutes.

[0066] Turn off all power and gas sources, maintain a vacuum environment inside the vacuum chamber, allow it to cool naturally to room temperature, open the vacuum chamber, remove the sample, and complete the entire preparation process.

[0067] Example 2: The surface of the workpiece substrate is treated by grinding and polishing. Specifically, the workpiece substrate is treated by grinding and polishing in sequence with 200# sandpaper, 400# sandpaper, 800# sandpaper, 1200# sandpaper, 2000# sandpaper and polishing cloth with polishing agent.

[0068] The surface of the workpiece substrate after grinding and polishing is cleaned by means of ultrasonic cleaning or alcohol wiping to remove surface adhering substances and obtain a clean workpiece substrate.

[0069] The cleaned workpiece substrate is placed into the process chamber of the PECVD deposition equipment to form a transition layer on the surface of the workpiece substrate to be coated. This process specifically includes: Evacuate the process chamber until the pressure is less than 6 × 10⁻⁶. -3 Pa, argon gas is introduced as a protective gas and plasma is ionized. During this process, the flow rate of argon gas is 150 sccm, the chamber pressure is adjusted to 1 Pa, the bias voltage is 1000 V, and the plasma cleaning is performed for 35 min. Argon flow rate is adjusted to 100 sccm, and tetramethylsilane is introduced into the process chamber as the first process gas for coating. The flow rate of tetramethylsilane is 10 sccm, the pressure in the process chamber is 1.5 Pa, the bias power supply is 150 V, and the coating time is 30 min. Argon flow rate is adjusted to 100 sccm. Tetramethylsilane is used as the first process gas and acetylene is used as the second process gas and introduced into the process chamber for coating. The flow rate of tetramethylsilane is 10 sccm and the flow rate of acetylene is 90 sccm. The pressure in the process chamber is 1.8 Pa, the bias power supply is 120 V, and the coating time is 5 min. Argon flow rate was adjusted to 100 sccm, tetramethylsilane flow rate was adjusted to 0 sccm, and acetylene was introduced into the process chamber as the second process gas for coating. The acetylene flow rate was 90 sccm, the pressure in the process chamber was 1.8 Pa, the bias power supply was 120 V, and the coating time was 5 min to obtain the transition layer.

[0070] Twenty deposition cycles were performed alternately for Si-DLC and C-DLC, with a total thickness of 40 nm per cycle; each Si-DLC layer was 20 nm thick; and each C-DLC layer was 20 nm thick.

[0071] The deposited thin film sample undergoes composite electromagnetic post-processing. The sample is clamped between two power supply electrodes 200 and surrounded by coils 110 (see...). Figure 3 After clamping and positioning, power is supplied to the power supply electrode 200 and the coil 110 respectively, and composite electromagnetic post-processing is performed in the process chamber, specifically including: In a vacuum environment, 10 sccm of argon gas is introduced, and the temperature is controlled to not exceed 200℃ and maintained at a constant temperature. The electric field power supply uses a pulsed DC power supply with a duty cycle between 30% and 60%, and the pulse width of the 10 pulses is between 50μs and 100μs, with a frequency between 1Hz and 50Hz. The impedance of the magnetic field coil is between 2Ω and 8Ω, and it is powered by 380V / 50Hz AC. It is equipped with a 0-10V DC adjustable control signal. The electric field strength is adjusted to 10V, and the magnetic field strength is 1.5T. The post-processing is maintained for 10 minutes.

[0072] Turn off all power and gas sources, maintain a vacuum environment inside the vacuum chamber, allow it to cool naturally to room temperature, open the vacuum chamber, remove the sample, and complete the entire preparation process.

[0073] like Figure 7 As shown, scanning electron microscopy was used to analyze the morphological changes at the interface. Figure 7 (a) in the image represents the thin film without post-composite electromagnetic processing. Figure 7 (b) in Figure 1 shows the thin film after composite electromagnetic post-treatment. Region A in Figure 1 corresponds to region A' in Figure 1 after composite electromagnetic post-treatment. The comparison shows that the thin film after composite electromagnetic post-treatment has obvious defect repair effect.

[0074] like Figure 8 As shown, Raman spectroscopy was used to detect compositional changes. The purple curve in the figure represents the overall spectral fit curve, the red curve represents the D-peak fit curve, and the green curve represents the G-peak fit curve. The peak intensity ratio of the D-peak to the G-peak is Ig. D / I G It can characterize the sp² / sp³ carbon ratio and the degree of carbon structural disorder within the thin film; I D / IG An increase in sp² graphite phase indicates an increase in the degree of graphitization of the thin film; I D / I G A decrease indicates a higher proportion of sp³ diamond phase, resulting in higher film hardness. Figure 8 (a) in the image is the Raman spectrum of the central region before composite electromagnetic post-processing. Figure 8 (b) in the image is the Raman spectrum of the edge region without composite electromagnetic post-processing. Figure 8 (c) in the image is the Raman spectrum of the central region after composite electromagnetic post-processing. Figure 8 Figure (d) shows the Raman spectrum of the edge region after composite electromagnetic post-treatment. Comparing Figure (a) and Figure (b), it can be seen that the peak positions and shapes of the D and G peaks in the central and edge regions of the film without composite electromagnetic post-treatment are significantly different, indicating that the carbon microstructure of the deposited film sample is not uniform at different locations, and there is a large deviation in the local sp² / sp³ carbon ratio of the film layer. After composite electromagnetic post-treatment, it can be seen from Figures (c) and (d) that the peak shapes and positions of the D and G peaks in the central and edge regions of the film tend to be consistent, and the overall carbon structure uniformity of the sample is significantly improved. The composite electromagnetic field promotes the rearrangement of carbon elements inside the film, reduces the difference in carbon hybridization state in different regions of the sample, and is beneficial to improving the consistency of the overall mechanical and tribological properties of the film.

[0075] like Figure 9 The adhesion strength was tested using a scratch adhesion test method. The upper curve (DLC film 10V+1.5T) represents the film treated with an electric field of 10V and a magnetic field of 1.5T, while the lower curve (DLC film) represents the film without electromagnetic post-treatment. The horizontal axis represents the applied load, and the vertical axis represents the scratch acoustic signal. The comparison revealed that the film without electromagnetic post-treatment exhibited a significant signal abrupt change at a load of approximately 55N, indicating film peeling failure. The film after electromagnetic post-treatment showed an increased critical failure load and a higher loading load corresponding to failure, demonstrating that electromagnetic post-treatment effectively improves the interfacial state of the film and significantly enhances the film adhesion.

[0076] like Figure 10As shown, tribological performance was tested using a reciprocating tribological testing machine. The purple curve (DLC film) represents the film without composite electromagnetic post-treatment; the red curve (DLC film 0V+1.5T) represents the film treated with an electric field strength of 0V and a magnetic field strength of 1.5T; the blue curve (DLC film 5V+1.5T) represents the film treated with an electric field strength of 5V and a magnetic field strength of 1.5T; and the black curve (DLC film 10V+1.5T) represents the film treated with an electric field strength of 10V and a magnetic field strength of 1.5T. The horizontal axis represents the tribological test time, and the vertical axis represents the coefficient of friction. The test load was 20N, and the test time was 120 minutes. The curves showing the change in the coefficient of friction of diamond-like carbon (DLC) films over time under different composite electromagnetic post-treatment conditions were compared. It was found that the coefficient of friction of the film without electromagnetic post-treatment increased sharply after about 88 minutes of friction testing, leading to rapid wear failure. The film with only a magnetic field applied, without an electric field, showed improved wear resistance compared to the film without electromagnetic post-treatment. The films treated with a composite electromagnetic post-treatment of 5V+1.5T and 10V+1.5T maintained a relatively low coefficient of friction and exhibited a more stable friction process. The 10V+1.5T composite electromagnetic post-treatment sample could withstand 120 minutes of friction testing, demonstrating the best wear resistance performance. Therefore, the composite electromagnetic post-treatment using a combination of electric and magnetic fields can improve the microstructure of the film and effectively enhance the wear resistance of diamond-like carbon (DLC) films.

[0077] The above are merely specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes, but is not limited to, the contents described in the accompanying drawings and the specific embodiments above. Any modifications that do not depart from the functional and structural principles of the present invention will be included within the scope of the claims.

Claims

1. A method for depositing a film on the surface of a workpiece substrate, characterized in that, The method includes: Provide workpiece substrate; A transition layer is formed on the surface of the workpiece substrate to be coated, wherein, along the direction away from the surface of the film to be coated, the silicon content of the transition layer gradually decreases and the carbon content gradually increases; A nanolayer is formed on the transition layer to obtain an initial workpiece. The nanolayer includes alternating functional diamond-like carbon (DLC) films and transitional DLC films, and the nanolayer includes at least two of the functional DLC films. Both the functional DLC films and the transitional DLC films are doped with silicon, and the mass percentage of silicon in the functional DLC films is greater than the mass percentage of silicon in the transitional DLC films. A magnetic field and an electric field are applied to the initial workpiece according to a set rule and maintained for a set time to obtain the target workpiece. In the target workpiece, the mass percentage of silicon in the functional diamond-like carbon film is greater than the mass percentage of silicon in the transition diamond-like carbon film. The SP content in the functional diamond-like carbon film... 3 The mass percentage of carbon is greater than that of sp in the transition diamond-like carbon film. 3 The percentage of carbon by mass.

2. The method according to claim 1, characterized in that, The initial workpiece is positioned between two power supply electrodes and in a magnetic field generated by a magnetic field assembly comprising multiple movable coils, the axial directions of the multiple coils being aligned, and the initial workpiece being positioned within a cavity defined by the multiple coils. In the step of applying a magnetic field and an electric field to the initial workpiece according to the set rules, the position of each coil is determined according to the set rules, and the power supply electrode and the magnetic field assembly are powered by a pulsed DC power supply.

3. The method according to claim 2, characterized in that, The duty cycle of the pulsed DC power supply is between 30% and 60%, the pulse width of the 10 pulses is between 50μs and 100μs, the frequency is between 1Hz and 50Hz, and the voltage is between 350V and 400V, so that the electric field strength is between 10V and 20V and the magnetic field strength is between 1T and 2T.

4. The method according to claim 1, characterized in that, The set time is between 5 minutes and 25 minutes.

5. The method according to any one of claims 1 to 4, characterized in that, Forming a nanolayer stack on the transition layer includes the following alternating steps: A functional diamond-like carbon (DLC) film is formed, wherein the silicon content in the DLC film is between 5 wt% and 15 wt%, and the sp... 3 The carbon content is between 60 wt% and 75 wt%. A transition diamond-like carbon (LDC) film is formed, wherein the silicon content in the transition diamond-like carbon film is between 1 wt% and 5 wt%, and sp... 3 The carbon content is between 50wt% and 60wt%.

6. The method according to claim 5, characterized in that, In the step of forming a functional diamond-like film, a protective gas, a first process gas, and a second process gas are introduced into the process chamber, wherein the first process gas contains silicon and the second process gas contains carbon. In the step of forming the transition diamond-like carbon film, the protective gas and the second process gas are introduced into the process chamber.

7. The method according to claim 6, characterized in that, The protective gas includes argon, the first process gas includes tetramethylsilane, and the second process gas includes acetylene. In the step of forming the functional diamond-like carbon film, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the first process gas is between 10 sccm and 12 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is between 1.0 Pa and 2.0 Pa, and the bias power supply in the process chamber is between 120 V and 150 V. In the step of forming the transition diamond-like carbon film, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is between 1.0 Pa and 2.0 Pa, and the bias power supply in the process chamber is between 120 V and 150 V.

8. The method according to claim 5, characterized in that, The single-layer thickness of both the functional diamond-like carbon film and the transition diamond-like carbon film is between 5 nm and 25 nm. The functional diamond-like carbon film and the transitional diamond-like carbon film are stacked alternately to form 5 to 20 cycles.

9. The method according to any one of claims 1 to 4, characterized in that, A transition layer is formed on the surface of the workpiece substrate to be coated, including: A protective gas is introduced into the process chamber and plasma-ionized to perform plasma cleaning on the workpiece substrate. In a protective gas atmosphere, a first process gas is introduced into the process chamber and deposited on the workpiece substrate, wherein the first process gas contains silicon. In the atmosphere of the protective gas, the first process gas and the second process gas are introduced into the process chamber and deposited on the workpiece substrate, wherein the second process gas contains carbon; In the atmosphere of the protective gas, the second process gas is introduced into the process chamber and deposited on the workpiece substrate.

10. The method according to claim 9, characterized in that, The protective gas includes argon, the first process gas includes tetramethylsilane, and the second process gas includes acetylene. Before the step of plasmaing the protective gas, the process chamber is first evacuated to ensure that the pressure inside the process chamber does not exceed 8 × 10⁻⁶. -3 Pa, In the step of plasmaing the protective gas, the pressure in the process chamber is maintained between 0.3 Pa and 1.2 Pa, the flow rate of the protective gas is between 140 sccm and 160 sccm, and the voltage of the bias power supply is between 500 V and 1500 V; In the step of depositing a first process gas on the workpiece substrate under a protective gas atmosphere, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the first process gas is between 10 sccm and 12 sccm, the pressure in the process chamber is maintained between 1.0 Pa and 2.0 Pa, and the voltage of the bias power supply is between 120 V and 150 V. In the step of introducing the first process gas and the second process gas into the process chamber under the atmosphere of the protective gas, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the first process gas is between 10 sccm and 12 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is maintained between 1.0 Pa and 2.0 Pa, and the bias voltage is between 120 V and 150 V. In the step of depositing the second process gas on the workpiece substrate by introducing the second process gas into the process chamber under the atmosphere of the protective gas, the flow rate of the protective gas is between 90 sccm and 110 sccm, the flow rate of the second process gas is between 60 sccm and 90 sccm, the pressure in the process chamber is maintained between 1.0 Pa and 2.0 Pa, and the bias voltage is between 120 V and 150 V.

11. The method according to any one of claims 1 to 4, characterized in that, In the step of applying a magnetic field and an electric field to the initial workpiece according to the set rules, the pressure in the process chamber is between 1 Pa and 5 Pa, and the temperature in the process chamber does not exceed 400°C.

12. A coated workpiece, the coated workpiece comprising a workpiece substrate (10), characterized in that, The coated workpiece further includes a transition layer (20) disposed on one side surface of the workpiece substrate (10) and a nano-stack (30) disposed on the side of the transition layer (20) away from the workpiece substrate (10). Along the direction away from the surface to be coated, the silicon content of the transition layer (20) gradually decreases and the carbon content gradually increases. The nano-stack (30) includes alternately arranged functional diamond-like carbon (DLC) films (31) and transition DLC films (32). In the coated workpiece, the mass percentage of silicon in the functional DLC film (31) is greater than the mass percentage of silicon in the transition DLC film (32). The silicon content in the functional DLC film (31) is... 3 The mass percentage of carbon is greater than that of sp in the transition diamond-like carbon film (32). 3 The percentage of carbon by mass.

13. The coated workpiece according to claim 12, characterized in that, In the functional diamond-like carbon film (31), the silicon content is between 5 wt% and 15 wt%, sp 3 The carbon content is between 60 wt% and 75 wt%, and the silicon content in the transition diamond-like carbon film (32) is between 1 wt% and 5 wt%. 3 The carbon content is between 50wt% and 60wt%.